DAMPAK PT. THERMOPACK KARYA INDONESIA TERHADAP KETENAGAKERJAAN DAN KARESIDENAN DI MAGELANG STUDI KASUS MANUFAKTUR PLASTIK DI INDONESIA - Afiifah Shofiana W; Rizki Firmansyah; Usman Zakaria; Ervina Martha Herawati (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Thermopak Karya Indonesia (PT. TKI) is a plastic packaging manufacturer established in 2018 in Magelang, Indonesia. The company has experienced significant growth and become a key player in the plastic packaging industry. Its presence has had a substantial impact on local employment and socioeconomic dynamics.This study examines the impact of PT. TKI on employment and community welfare in Magelang. It focuses on the company's influence on workers' quality of life, challenges faced in employment and sustainability, and its contribution to local development.This study examines the impact of PT. TKI on employment and community welfare in Magelang. It focuses on the company's influence on workers' quality of life, challenges faced in employment and sustainability, and its contribution to local development. A descriptive-analytical juridical-normative method is employed to provide a comprehensive understanding of PT. TKI's role in enhancing socioeconomic well-being in Magelang. PT. TKI has significantly contributed to employment creation, income improvement, and social development in Magelang. The company implements international standards (ISO 9001 and ISO 22000) and engages in CSR initiatives to support the community. However, challenges remain in terms of minimum wages, working conditions, and environmental impact.PT. TKI plays a crucial role in Magelang's economic development and social welfare. While addressing employment and environmental concerns, the company's commitment to social responsibility and sustainability is essential for long-term success.